2020
DOI: 10.3390/plants9091084
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Response of Alternanthera bettzickiana (Regel) G. Nicholson under Acetic Acid Assisted Phytoextraction of Lead

Abstract: Heavy metals (HMs) stress causes severe damage to physiology and biochemistry of plant species leading to stunted growth and low yield. Phytoremediation via phytoextraction, a viable low-cost and environment-friendly alternative to other techniques that are often too expensive, impractical and hazardous. However, phytoextraction potential, physiological and biochemical response of various plant species against HMs stress is not fully understood. Among other HMs, lead (Pb) is an inorganic pollutant with deleter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Since the accumulation of HMs in the plants leads to adverse changes in the primary photosynthetic organ leaves, a decline in the rate of photosynthesis can be presumed. Literature hints that the impact of HMs on photosynthetic machinery depends on the reactivity and concentration of HMs in leaves, which subsequently affects light capture, electron transport, and activities of photosynthetic enzymes including RuBisCO ( Figure 2 ) [ 71 , 72 , 73 ].…”
Section: Hm Toxicity Negatively Influence the Photosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Since the accumulation of HMs in the plants leads to adverse changes in the primary photosynthetic organ leaves, a decline in the rate of photosynthesis can be presumed. Literature hints that the impact of HMs on photosynthetic machinery depends on the reactivity and concentration of HMs in leaves, which subsequently affects light capture, electron transport, and activities of photosynthetic enzymes including RuBisCO ( Figure 2 ) [ 71 , 72 , 73 ].…”
Section: Hm Toxicity Negatively Influence the Photosynthesismentioning
confidence: 99%
“…Other plants experiencing toxicity of a variety of HMs also showed a similar drop in the photosynthesis and all of these studies collectively suggested that the decline in photosynthesis is majorly because of the decrease in the chlorophyll concentrations. Based on the literature evidence, it can be concluded that HMs can target chlorophyll in any of three ways: (1) by enhancing the activity of chlorophyllase enzyme [ 73 ]; (2) by causing oxidation/reduction of chlorophyll molecules by the HM toxicity induced ROS [ 78 , 79 , 80 ]; and (3) inhibition of chlorophyll biosynthesis as some of the HMs such as Hg, Cu, Pb, Ni, Cd, and Zn are able to replace the Mg in the porphyrin ring of the chlorophyll molecules [ 45 , 74 , 81 , 82 , 83 , 84 , 85 ]. Besides, phaeophytization of chlorophyll molecules because of the replacement of Mg 2+ ions by H + ions has also been reported in Eudorina unicocca and Chlorella kessleri under Cr-toxicity [ 86 ].…”
Section: Hm Toxicity Negatively Influence the Photosynthesismentioning
confidence: 99%
“…The plants were sprayed with different concentrations of glyphosate beginning after one week of glyphosate purchase and with 5 replicates per condition and 60 replicates per experiment. Levels of chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids were determined spectrophotometrically [17]. After treatment, the topmost fully expanded leaves were weighed and dipped in 85% (v/v) aqueous acetone to extract chlorophyll pigments.…”
Section: Samplesmentioning
confidence: 99%
“…Absorbances at 452.5 nm, 644 nm, and 663 nm were then measured relative to a blank sample of 85% liquid acetone. Levels of chlorophyll a and b, total chlorophyll, and carotenoids were determined spectrophotometrically using the following equations (where E stands for absorbance at the indicated wavelength) [17]: The absorbance of centrifuged, transparent acetone over the range of 380-700 nm was estimated using Spectrophotometer (JASCO Model V-670).…”
Section: Samplesmentioning
confidence: 99%
“…Chromium (Cr) is a toxic metal which is mainly released from tanning industries [ 3 ]. It is both a toxic and a non-essential element [ 6 ]. Plants have specific transporters for the uptake and transport of mineral ions required for various metabolic processes.…”
Section: Introductionmentioning
confidence: 99%